A 0.1% L-Menthol mouth swill in elite male rugby players has different effects in forwards and backs - Jerram, M. L.; Baker, D.; Smith, T. B.; Healey, P.; Taylor, L.; Black, K. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Menthol mouth swills can improve endurance performance in the heat, which is attributed to attenuations in nonthermally derived thermal sensation (TS) and perception of effort. However, research in elite team-sport athletes is absent. Therefore, this study investigated the performance and TS responses to a 0.1% menthol mouth rinse (MR) or placebo (PLA) among elite male rugby union players.